Aktivitas Emulgel Ekstrak Teripang (Stichopus horrens) Terhadap Penyembuhan Luka - Lili Sartika; Aulia Chintara; Ikha Rahardiantini; Masyitah Novia Yanti (Universitas Respati Indonesia, 2026)
A wound is a form of skin tissue damage caused by contact with a heat source (such as chemicals, fire, hot water, electricity, and radiation), medical procedures, or changes in physiological conditions. Wound treatment depends on the extent of the wound. The deeper the affected skin layer, the longer it takes. To reduce unwanted side effects, many people turn to herbal medicine, one of which is the use of sea cucumbers. The purpose of this study was to determine the activity of sea cucumber (Stichopus horrens) extract emulgel on wound healing compared to betadine ointment. The research method used a true experimental design. This study used 30 male white mice (Mus musculus). The results showed that sea cucumber (Stichopus horrens) extract can accelerate the wound healing process in incisions on the skin of mice. Wound healing is caused by bioactive compounds such as saponins, flavonoids, lectins, and amino acids that play a role in accelerating the wound healing process.